Preoperative Short-Course Radiotherapy and Surgery versus Surgery Alone for Patients with Rectal Cancer: A Propensity Score-Matched Analysis at 18-Year Follow-Up - Pach, Radoslaw (Biomedicines, 2021)
A significant problem for long-term rectal cancer survivors may be the late toxicity of radiotherapy. It creates the possible risk of developing second primary malignancy and a theoretical decrease in overall survival. This study aimed to assess the influence of short-course preoperative radiotherapy in patients with locally advanced rectal cancer on overall survival, local recurrence rate, and second malignancy at 18-year follow-up. The rectal cancer trial was conducted in a single tertiary center between February 1992 and June 2006. A total of 389 patients with locally advanced rectal cancer (cT2-cT4, cN0/+, cM0) were included in the study. Preoperative radiotherapy was conducted in 148 patients and 241 patients underwent surgery alone. The propensity-matched group consisted of 105 patients operated on after radiotherapy and 105 controls. The number of local recurrences was 7 (6.7%) in the preoperative radiotherapy group and 22 (21%) in the surgery alone group (p = 0.016). The 18-year survival analysis showed no survival benefit in the preoperative radiotherapy group (38% versus 48%, p = 0.107) but improved recurrence-free survival (81% versus 58%, p = 0.001). The preoperative short-course radiotherapy significantly decreases the risk of local recurrence in locally advanced rectal cancer and may improve recurrence-free survival without an increased risk of second primary malignancy.